An Experiment on Three Different Restorative Materials in the Management of Class V Non-Carious Cervical Lesions (Journal of Preventive and Social Medicine, 2026)
Background: To obtain the best performance in management of non-carious cervical lesion, many restorative materials and technique have tried. The success of the treatment depends on the materials which should be identical to natural tooth structure, adhesive, abrasion resistance, good marginal integrity with excellent surface texture. Hypothesis: The clinical application and performance of Giomer is superior to Flowable composite and Resin modified glass ionomer cements (RMGIC) in the management of class v non-carious cervical lesions. Objectives: Evaluation of the clinical performance of Giomer, Flowable Composite and Resin Modified Glass Ionomer Cements (RMGIC)in the management of class v non-carious cervical lesions. Methods: An experimental was done among thirty-two healthy adult having at least three non-carious cervical lesions on buccal surface (size 1-2mm) of teeth were selected for the study. The method of sampling was simple random sampling by lottery method. After clinical evaluation, 150 teeth were selected. These 150 samples were divided equally into three groups.  Group 1: Giomer, Group 2: Flowable Composite and Group 3: Resin Modified Glass Ionomer Cement. Restoration was assessed by Modified Ryge’s Criteria by means of retention, color matching, marginal integrity and surface texture. Patients were recalled after 3, 6, and 12 months for follow up observation. Statistical analysis was performed by one way ANOVA and Tukey’s post hoc test, where p value < 0.05 was considered as statistically significant. Results: The result of this study showed that at 12 months follow up, the retention was 48(93.8%), 43(87.5%) and 43(91.5%) for Giomer, Flowable Composite and RMGIC, respectively. There were no statistically significant differences among the retention ability of these materials. Regarding color matching, Giomer and Flowable composite were more color stable than RMGIC (p< 0.05) where statistically significant difference were observed. The marginal integrity of Giomer was also significantly better than RMGIC (p